TEMPORAL CHANGE DETECTION OF LAND USE/LAND COVER USING GIS AND REMOTE SENSING TECHNIQUES IN SOUTH GHOR REGIONS, AL-KARAK, JORDAN - Mohd Khairul Amri, Kamarudin; Abdul Rahman, Hasan; Fathurrahman, Lananan (2018)
This study examines the spatial and temporal changes of land use and land cover in South Ghor, Jordan. Satellite images for the years 1972, 1989, 1999 and 2016 were used for LULC supervised classification techniques, four LULC classes were decided: built-up areas, pastures and bare land, agricultural land and water bodies. For the accuracy of assessment classifications, matrix error and KAPPA analysis have been used in this paper. The analysis detected by supervised classification techniques show that agricultural land and built-up land have increased, while barren land and water bodies have decreased. It is predicted that the study would significantly contribute to better policy making, sustainable development and developing useful change detection planes for the south ghor regions and similar regions of the country.